The Mozart effect on spatial-temporal reasoning skills recommendations for a musically-enhanced pre-school library - Jamin, Raymond P.; Yang, Jackson V. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2001)
The library is an important venue in the learning process and the aim of this research is to further enhance the "learning experience" in the said venue. Music has often been believed to possess many qualities that can enhance the physical, emotional and mental capabilities and capacities of human beings.
This research thrust is therefore to incorporate music in a learning institution such as a library. In 1993 a study conducted by Frances Rauscher, Ph.D. a Professor in the University of California in Irvine and her colleagues, was able to shed some light on some important aspects of music and the learning process. They found out that Mozart's music has an effect on spatial-temporal reasoning abilities, the ability to visualize physical objects in the brain.
A similar study was then conducted adopting some of the key concepts of the previously mentioned research. The results, although not necessarily significant, was able to show that for the sample group of pre-school students, Mozart's music has a more positive effect compared to relaxation music or to no music at all.
Several recommendations were then given with regards to using Mozart's pieces to musically enhance a pre-school library
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Children's libraries -- Philippines; Music -- Psychological aspects